Evaluation of Film Thickness of Crown Disclosing Agents and Their Comparison with Cement Film Thickness after Final Cementation - Habib, Syed Rashid; Ansari, Abdul Sadekh; Bajunaid, Salwa Omar; Alshahrani, Abdullah; Javed, Muhammad Qasim (European Journal of Dentistry, 2020)
Objective Verification of the accuracy of crown fit before final cementation is imperative. The aim of this in vitro study was to evaluate the film thickness of commonly used dental crown disclosing materials and their comparison with final cement thickness.Materials and Methods One hundred fifty provisional crowns (Protemp) were fabricated on standardized resin dies and divided into five groups (N = 150; n = 30) based on five disclosing agents: A = Fit-Checker auto-mix; B = Okklu-top; C = Express; D = Fit-Checker hand-mix; E = Coltene PSI, and Final cement = Relyx U200. Crowns were loaded with test materials, tried over dies under load (50N), and later cemented under same load. Film thickness (µm) was recorded between crown margin and the finish line of die after loading with test material and final cementation using a digital microscope.Statistical Analysis Descriptive statistics, analysis of variance, Tukey’s and paired t-test were used for statistical analysis (p < 0.05).Results Significant variations were found between the film thicknesses of the five disclosing agents (p = 0.019). Group-A showed the lowest (131.67 ± 101.10 μm), while group-B (295.00 ± 263.88 μm) showed the highest film thickness (p = 0.011). Film thicknesses after cementation were similar for groups (p = 0.957). Significant difference was observed for group-B disclosing agent versus final cement (p = 0.010). The lowest mean difference between the film thicknesses of the disclosing agent and final cementation of 13.1 μm was revealed for group-A.Conclusions Variations in the film thicknesses of the tested disclosing agents were found. Fit-Checker auto-mix was found with minimal film thickness and satisfied the requirements as the disclosing agent, while Okklu-top aerosol spray did not.
Keywords: disclosing methods; fit checker; crown fit; dental crowns; dental crown disclosing materials; cement thickness; cementation; dental cement